ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PETANIMENGUSAHAKAN PADI ORGANIK DAN PADI ANORGANIK DI DESA SUMBERSUKO JAYA KECAMATAN BELITANG KABUPATEN OKU TIMUR - Adi Subakti, Mas; Kurniawan, Rahmat (Muhammadiyah University of Palembang, 2015)
This research aims to analyze background factors the rice farmers Sumbersuko Jaya villageto cultivates organic and inorganic rice and to analyze the difference of rice farming income between organic rice farmers and inorganic rice farmers.Research methods used in this research was a case study. Method of sampling used was the method of Disproportionate stratified random sampling, with total sample 40 farmers were divided into two groups, i.e. organic rice farmers was as much as 20 farmers and groups II was the rice farmers were as much as 20 farmers. Data collection methods used were interviews and observations. Data obtained in the field, was grouped and then processed with Tabulation method. To answer the first problem was used logit regression equation model. To analyze the second problemwith comparing income of organic rice farmers and inorganic rice farmers was usedanalysis parametric t-test. Statistical tests with using the SPSS computer applications programs for windows 19.00.Research results show that the income of farming rice (organic and inorganic), educational level non signifikan to farmers decision. Family number, land area of farmers signifikan to farmers decision. The organic rice farmers income was more than inorganic rice farmers per hectare per season.